ARTISTIC FEATURES OF CREATING THE IMAGE OF “AN EXTRA PERSON” IN THE WORKS OF I.S.TURGENEV - Abdullayev Khusan Abdushukurovich; Pardaeva D. R. (American Journals Publishing, 2023)
This article discusses the artistic features of creating the image of an «extra person» and the place of an extra person in Turgenev's work, also considers the main meaning of the image, and the creation of an artistic image.
Keywords: Image, artistic image, image creation, extra person.